2011
DOI: 10.1007/s12306-011-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the flexor superficialis tendon of ring finger: a case report and review of literature

Abstract: Compared with flexor digitorum profundus (FDP) tendon injury, the isolated rupture of flexor digitorum superficialis (FDS) tendon in a finger is a rare report in the literature. The pathogenesis is still unclear if we consider only tendon rupture without congenital anomalies or other diseases. The diagnosis is clinical, but it can be confirmed by ecography or magnetic resonance imaging (MRI). We report the case of a flexor superficialis (FS) tendon closed rupture of the ring finger of right hand in a 57-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In the literature, there are several case reports of FDS tendon rupture during activities other than climbing [22][23][24][25][26][27][28][29]. Boyes et al [30] performed a literature review of spontaneous flexor tendon rupture and found that 12% of reported ruptures involved only the FDS tendon (n = 9/80); 10% occurred in the middle finger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are several case reports of FDS tendon rupture during activities other than climbing [22][23][24][25][26][27][28][29]. Boyes et al [30] performed a literature review of spontaneous flexor tendon rupture and found that 12% of reported ruptures involved only the FDS tendon (n = 9/80); 10% occurred in the middle finger.…”
Section: Discussionmentioning
confidence: 99%
“…These tendon forces were estimated using the musculoskeletal model, using the grip forces and joint angles of the elite climber as input. others resection [22][23][24]29], while others prefer functional treatment with physiotherapy [26,27,30] with equally disparate results. Faced by the unusual diagnostic delay in the present case, it seemed reasonable to us to first attempt functional treatment with a patient who presented few symptoms 20 days after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Boyes et al published a review in 1960, on flexor tendon injuries in the hand, and cited that only 3 out of 80 cases examined could be considered spontaneous, which he defined as “ruptures which were not directly related to underlying or associated pathological changes.”5 A review of literature conducted by Bois et al 1 demonstrated that in the past 50 years, 43 cases (including 50 spontaneous tendon ruptures) have been published, showing that these were unique compared with the more common ruptures that result from avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…O'Sullivan et al [29] presented a case of bilateral, but not simultaneous FDP tendon rupture in the index fingers at the junction of zones II and III. Isolated spontaneous ruptures of the FDS tendons have been reported less frequently as isolated case histories [2,20,24,33]. They tend to present late and may be underdiagnosed, possibly because there is little functional limitation.…”
Section: Discussionmentioning
confidence: 99%